ANALISIS PERENCANAAN KEBUTUHAN INFORMASI DALAM PEMBELAJARAN MATEMATIKA PADA ERA DIGITAL DI SD NEGERI 2 JATIBANTENG SITUBONDO - Yovita Puspasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The education sector has a crucial role in the nation's progress. The progress of the times which is marked by rapid technology can actually facilitate access and educational activities, including the learning process. Meeting information needs in all subjects, including mathematics, can run smoothly in the digital era and at all levels of education, especially at the elementary school (SD) level. Mathematics subjects are often seen as difficult because students are bored with the learning methods applied by teachers. This research aims to identify planning information needs in mathematics learning in the digital era at SD Negeri 2 Jatibanteng Situbondo. The research method used is a qualitative descriptive method through observation, interviews and literature study. Based on the research results, it was found that planning and fulfilling information needs in the learning process still faces various limitations and challenges, such as a lack of teacher competence and inadequate technology available. Some of these obstacles make students interest and activeness in mathematics subjects decrease so that the learning process becomes boring.